Segmental Arterial Dissection with Spinal Cord Ischemia in Surfer’s Myelopathy - Alejandro M. Brunser,; Sofia González,; Felipe Vial,; Florencia Alamos,; Marcela Valenzuela,; Paulo Zúñiga,; Pablo Lavados, (Journal of Vascular and Interventional Neurology, 2023)
Background— The etiology of surfers’ myelopathy is not well understood. We report upon two patients who underwent acute spinal vascular angiographic imaging. Case Description— A 20-year-old man and 32-year-old man presented with paraplegia or paraparesis after surfboard maneuvers. Segmental artery occlusion with pencil-shaped termination, suggestive of arterial dissection, was identified in both patients on spinal angiograms performed within 96 hours of symptom onset. Conclusions— Our report identifies segmental arterial dissection with spinal cord ischemia as the underlying process for surfer’s myelopathy.